Upaya Meningkatkan Keterampilan Komunikasi Siswa dalam Pembelajaran Sejarah melalui Strategi Giving Question Getting Answer - Ulfi Indriyani (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2020)
This research aimed to improve students communication skill in learning history by implementing Giving Question Getting Answer Strategy. Based on pre-research observations showed the lack of communication skill of students in learning history. The problem emerged because, in the learning process, communication conducted in one direction. Therefore, researchers conducted the Classroom Action Research method with Kemmis-Taggart design which includes four activities to be carried out in each cycle, namely plan, act, observe, and reflect. Data collecting technique that used in this research were observation, field notes, interviews and documentation studies. The indicators consisted of asking questions, presenting information, draw a conclusion, presentation clarity, mastery of subject matter, interaction in the group and giving feedback, which was developed into three sub-indicators. All of those aspects have experienced a good increase in each cycle. The average percentage of overall indicator score in Cycle I was 47,2%, then it increased in Cycle II to 68,3%, in Cycle III it increased again to 82%, add in Cycle IV it reached 92,8%. Thus, it can be concluded that students communication skill in learning history can be improved after the implementation of Giving Question Getting Answer strategy in four-cycle.